Ab initio investigation of competing antiferromagnetic structures in low Si-content FeMn(PSi) alloy. (3rd May 2016) - Li, Guijiang; Eriksson, Olle; Johansson, Börje; Vitos, Levente
Abstract: The antiferromagnetic structures of a low Si-content FeMn(PSi) alloy were investigated by first principles calculations. One possible antiferromagnetic structure in supercell along the c -axis was revealed in FeMnP0.75 Si0.25 alloy. It was found that atomic disorder occupation between Fe atom on 3f and Mn atoms on 3g sites is responsible for the formation of antiferromagnetic structures. Furthermore the magnetic competition and the coupling between possible AFM supercells along the c and a -axis can promote a non-collinear antiferromagnetic structure. These theoretical investigations help to deeply understand the magnetic order in FeMn(PSi) alloys and benefit to explore the potential magnetocaloric materials in Fe2 P-type alloys.